Exploring English Vocabulary Learning Strategies of Students in a Private Senior High School in East Jakarta - Alifah, Alya Nur; Wijirahayu, Suciana (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study examines the vocabulary learning strategies of grade 11 students at a private high school in East Jakarta, focusing on four categories: cognitive, metacognitive, memory and activation strategies. Using a quantitative descriptive method, data was collected from 169 students attending English classes. The data was collected using a questionnaire with a Likert scale and open-ended questions. The questionnaire consisted of 4 vocabulary learning strategies items: Cognitive Strategy, Metacognitive Strategy, Memory Strategy, and Activation Strategy. Each item consisted of 10 questions. The findings showed a diversity in strategy use, with digital tools and contextual inference being the most frequently used cognitive strategies. Metacognitive strategies such as goal setting and self-assessment were not consistently applied, while memory strategies such as repetition and auditory reinforcement proved effective for vocabulary retention. Activation strategies, including using new words in online conversations and interactions, highlighted the integration of technology in learning. This research emphasizes the importance of diverse and targeted teaching strategies to improve students' vocabulary acquisition and overall English proficiency.